2013
DOI: 10.1016/j.ad.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics and health-related quality of life of patients with moderate-to-severe psoriasis: The VACAP study

Abstract: The principal factor related to HRQoL in patients with psoriasis is the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
16
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
8
16
1
1
Order By: Relevance
“…Confirming these results, disease activity determined using a visual analog scale showed a correlation with the DLQI and the PASI [31]. Several studies confirmed the finding that improvements in HRQoL were linked to the enhancements of clinical manifestations of the disease [19,22,32], and identified disease severity (assessed by the PASI) as a predictor of HRQoL [21][22][23][24][25] (Table 4). In line with these results, the determinants of HRQoL measured by the DLQI indicated that a one-unit increase in PASI from the mean would increase the DLQI score by 0.29 (p = 0.002) [33].…”
Section: Hrqol and Disease Characteristicsmentioning
confidence: 64%
See 4 more Smart Citations
“…Confirming these results, disease activity determined using a visual analog scale showed a correlation with the DLQI and the PASI [31]. Several studies confirmed the finding that improvements in HRQoL were linked to the enhancements of clinical manifestations of the disease [19,22,32], and identified disease severity (assessed by the PASI) as a predictor of HRQoL [21][22][23][24][25] (Table 4). In line with these results, the determinants of HRQoL measured by the DLQI indicated that a one-unit increase in PASI from the mean would increase the DLQI score by 0.29 (p = 0.002) [33].…”
Section: Hrqol and Disease Characteristicsmentioning
confidence: 64%
“…In this sense, the effect of stigmatization on HRQoL was driven by a combination of symptom severity and stigmatization, suggesting that the effects of the latter on HRQoL were strongly associated with the emotional component of HRQoL [18]. Conversely, optimism correlated negatively with the overall score on the Skindex-29, thus indicating that the stronger the optimism is, the better the HRQoL will be [22,24].…”
Section: Hrqol and Patients' Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations